Symbolism and the quest for a new social awareness in Khaled Hosseini’s A Thousand Splendid Suns (2007) - Kesuwo, Anna Kelvin (Research Journal in Advanced Humanities, 2021)
This paper dwells on symbolism and a quest for a new social awareness in Khaled Hosseini’s novel. The work surveys the condition of women in Afghanistan and how Hosseini uses symbols to create certain emotions and moods in his work. Khaled Hosseini provides a brilliant portrait of a country shattered by a series of ideological leaders and wars imposed on it by foreign and internal forces. Furthermore, he uses pen to portray the life in the war-ravaged Afghanistan, Hosseini’s female characters just like the country of Afghanistan, appear to be propelled by the impulse of outside forces and society with little chance of influencing their own lives and futures.